Annunciation. - Stone, George Eathl (photographer):::Creator::::::::::::
This image depicts an Annunciation altarpiece, from Siena Cathedral, 1333 (frame reconstructed in the 19th century). Tempera and gold leaf on wood, center panel 10′ 1″ X 8′ 8 3/4″. Galleria degli Uffizi, Florence (1283? - 1344/5).